Editor's Choice – Angulation of the C-Arm During Complex Endovascular Aortic Procedures Increases Radiation Exposure to the Head. Issue 4 (April 2015) - Albayati, M.A.; Kelly, S.; Gallagher, D.; Dourado, R.; Patel, A.S.; Saha, P.; Bajwa, A.; El-Sayed, T.; Salter, R.; Gkoutzios, P.; Carrell, T.; Abisi, S.; et al.
Abstract : Objectives/Background: The increased complexity of endovascular aortic repair necessitates longer procedural time and higher radiation exposure to the operator, particularly to exposed body parts. The aims were to measure directly exposure to radiation of the bodies and heads of the operating team during endovascular repair of thoracoabdominal aortic aneurysms (TAAA), and to identify factors that may increase exposure. Methods: This was a single-centre prospective study. Between October 2013 and July 2014, consecutive elective branched and fenestrated TAAA repairs performed in a hybrid operating room were studied. Electronic dosimeters were used to measure directly radiation exposure to the primary (PO) and assistant (AO) operator in three different areas (under-lead, over-lead, and head). Fluoroscopy and digital subtraction angiography (DSA) acquisition times, C-arm angulation, and PO/AO height were recorded. Results: Seventeen cases were analysed (Crawford II–IV), with a median operating time of 280 minutes (interquartile range 200–330 minutes). Median age was 76 years (range 71–81 years); median body mass index was 28 kg/m 2 (25–32 kg/m 2 ). Stent-grafts incorporated branches only, fenestrations only, or a mixture of branches and fenestrations. A total of 21 branches and 38 fenestrations were cannulated and stented. Head dose was significantly higher in the PO compared with the AO (median 54 μSv [range 24–130 μSv] vs. 15 μSv [range 7–43 μSv], respectively; p  = .022), as was over-lead body dose (median 80 μSv [range 37–163 μSv] vs. 32 μSv [range 6–48 μSv], respectively; p  = .003). Corresponding under-lead doses were similar between operators (median 4 μSv [range 1–17 μSv] vs. 1 μSv [range 1–3 μSv], respectively; p  = .222). Primary operator height, DSA acquisition time in left anterior oblique (LAO) position, and degrees of LAO angulation were independent predictors of PO head dose ( p  < .05). Conclusions: The head is an unprotected area receiving a significant radiation dose during complex endovascular aortic repair. The deleterious effects of exposure to this area are not fully understood. Vascular interventionalists should be cognisant of head exposure increasing with C-arm angulation, and limit this manoeuvre.